Modern Art History on Italian Renaissance Portraiture: Topical Methodologies and Issues of Research - Zakharova, Vera N. (Actual Problems of Theory and History of Art, 2013)
This article deals with the issues of research and interpretation of Italian Renaissance Portraiture in art history of the 1970’s – 2000’s in European, American and Russian academic traditions (new social history of art, feminist history of art and queer-studies). The main object of the paper is the cluster of scholarly texts, discussing problems of the independent easel portraits mostly.
Keywords: portraiture; Italian Renaissance art; historiography